Future Fertility of Patients With No Embryo Transfer in Their First IVF Cycle Attempts - Zhu, Xuli; Cao, Mingya; Yao, Zhaohui; Lu, Peiyang; Xu, Yueming; Hao, Guimin; Zhao, Zhiming (Frontiers in Endocrinology, 2022)
Objective: We aim to evaluate the future outcomes of patients undergoing their first IVF (in vitro fertilization) attempt with no oocyte retrieved, no normal zygotes formed, or no embryos available to transfer, and to identify factors those might predict patients who will get a live baby. Methods: We retrospectively analyzed the dates of patients who underwent no transplantable embryo in their first IVF cycles attempt and carried out several consecutive cycles between January 2012 to December 2020. Frist, according to the reasons of cancellation, patients were divided into three groups：group A (no egg retrieval)，group B ( no normal zygotes formed), group C (no embryos available to transfer). Second, we divided patients into live birth group and no-live birth group according to whether they got a live baby or not. The clinical data and the cumulative clinical outcomes of groups were compared. Results:496 patients met the inclusion criteria, with no oocytes retrieved (group A), no normal zygotes formed (group B), or no embryos available to transfer (group C) in first IVF cycle. The age (34.1vs31, 34.1vs32, P<0.05) and base FSH level (13.1vs10.5, 13.1vs10.01, P<0.05) of women in group A were higher than those in group B and C. The stable cumulative live birth rate (CLBR)/patient of three groups achieved 18.18% (after 5 cycles, group A), 28.98% (after 3 cycles, group B) and 20.25% (after 7 cycles, group C). Moreover, the multivariate regression analysis showed that female age and basic FSH were main factors affecting live birth outcome of patients with no embryo transfer in their first IVF cycle attempts. Conclusions: The future clinical outcome of women with no normal zygotes is better than those with no oocyte retrieved and no available embryo at their first IVF cycle attempts. The main factors influencing their live birth are still age and ovarian reserve.